Features of bacterial-mycotic dysbiosis in women with high oncogenic risk human papillomavirus suffering from cervicitis, erosion and cervical dysplasia - Al Kasi Мae Ghazi (Zaporozhye State Medical University, 2014)
Aim. A possible relationship between the uterine neck dysplasia and vaginal microbiocenosis has been subject for broad discussions for many years. Hence, research devoted to the study of the problem of cervical lesions, in particular the progression of cervicitis, cervical erosion and cervical dysplasia depending on the ratio of obligate, opportunistic pathogenic and pathogenic microorganisms is of particular importance and relevance today. Methods and results. To address the problem, we have conducted a complete examination and studied the peculiarities of the opportunistic and pathogenic microfl ora spectrum in the urogenital tract microbiota in case of 120 female patients of reproductive age suffering from cervicitis, cervical erosion or cervical dysplasia on the background of Papilloma Viral Infection. The control group included 30 apparently healthy women. Conclusion. It was set, that dysbiosis forms in 52,1% women, in this 38,8% patients have moderate and 13,3% patients have severe dysbiosis. Anaerobic type of dysbiosis was verifi ed in 22,9% women and in 29,2% it was mixed aerobic-anaerobic type. Gardnerella vaginalis/Prevotella bivia/Porphiromonas spp., Eubacterium spp., Megasphaera spp./Veilonella spp./Dialister spp., Peptostreptococcus spp. were prevalent urogenital microbiota. Ureaplasma (urealiticum parva) was verifi ed in 23,8% patients and diagnostically meaningful it was in 20,0%, Candida spp. was 64,6 and 54,6% accordingly.